Does soil aging affect the N2O mitigation potential of biochar? A combined microcosm and field study. Issue 5 (28th October 2016) - Hagemann, Nikolas; Harter, Johannes; Kaldamukova, Radina; Guzman‐Bustamante, Ivan; Ruser, Reiner; Graeff, Simone; Kappler, Andreas; Behrens, Sebastian
Abstract: The application of biochar as a soil amendment to improve soil fertility has been suggested as a tool to reduce soil‐borne CO2 and non‐CO2 greenhouse gas emissions, especially nitrous oxide (N2 O). Both laboratory and field trials have demonstrated N2 O emission reduction by biochar amendment, but the long‐term effect (>1 year) has been questioned. Here, we present results of a combined microcosm and field study using a powdered beech wood biochar from slow pyrolysis. The field experiment showed that both CO2 and N2 O emissions were still effectively reduced by biochar in the third year after application. However, biochar did not influence the biomass yield of sunflower for biogas production ( Helianthus annuus L.). Biochar reduced bulk density and increased soil aeration and thus reduced the water‐filled pore space (WFPS) in the field, but was also able to suppress N2 O emission in the microcosms experiment conducted at constant WFPS. For both experiments, biochar had limited impact on soil mineral nitrogen speciation, but it reduced the accumulation of nitrite in the microcosms. Extraction of soil DNA and quantification of functional marker genes by quantitative polymerase chain reaction showed that biochar did not alter the abundance of nitrogen‐transforming bacteria and archaea in both field and microcosm experiments. In contradiction to previous experiments, this study demonstrates the long‐term N2 O emission suppression potential of a wood biochar and thus highlights its overall climate change mitigation potential. While a detailed understanding of the underlying mechanisms requires further research, we provide evidence for a range of biochar‐induced changes to the soil environment and their change with time that might explain the often observed N2 O emission suppression.